Territorialization, Control and Land Grabbing for the Implementation of an Agro-Industrial Model in the Colombian Altillanura - Ñáñez Ortiz, Paula Jimena; Calle Alzate, Laura (Geopolítica(s). Revista de estudios sobre espacio y poder, 2022)
This article analyzes the relationship between the control of the land, the exercise of violence and its correlation with territorialization processes based on dispossession, hoarding, enclosure and legalization of land from a temporal and spatial dimension. Based on a recent case study such as that of the El Brasil farm, the lands of La Fazenda in the Colombian Altillanura, it exposed how the properties belonging to the ancestral territory of the indigenous communities, recognized as vacant territories, were adjudicated by the State to peasants dispossessed by armed groups to be accumulated, marketed and legalized for agro-industrial exploitation later. From a qualitative documentary study, it is suggested that peasant and indigenous communities are dispossessed of the land and subjected to new forms of capitalist relationship within the framework of a rural development model that privileges agribusiness, emphasizing in the examination of the socio-historical and geographical relations of the inequalities that make possible and maintain dispossession.
Keywords: land control; territorialization; dispossession; armed conflict; agroindustry